Theoretical approaches to the annotations and stage notes in José Saramago's A Noite - Alma Delia Miranda Aguilar (Études romanes de Brno)
Regarding A Noite, José Saramago's first play, criticism has focused on conceptual aspects, particularly its themes and their recurrence alongside the author's works. Nevertheless, little has been written about theoretical approaches centered on the formal aspects of the play. The Carnation Revolution's 50th anniversary presents a good opportunity to approach the author's first work as one that portrays tensions over the mastery of words during Portugal's final years of the dictatorship. Thus, I will focus on the author's speech visible in stage directions as explicit (annotations) and implicit (stage notes) elements that will come to life through performance. The theoretical framework for what was previously stated is Semiología de la obra dramática (Semiology of the Play) by María del Carmen Bobes Naves.